2013
DOI: 10.1371/journal.pone.0073922
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recovery Patterns and Limited Spillover of Large Predatory Fish in a Mediterranean MPA

Abstract: Based on 19 y of visual census data from the Medes Islands MPA (NW Mediterranean), this study analyzes the carrying capacity (K) and population recovery time of six species of fish strongly affected by harvesting pressure along the Mediterranean coast. Three of these species (Epinephelus marginatus, Diplodus cervinus and Dicentrachus labrax) have practically reached carrying capacity in the Medes Islands MPA, while others are still approaching population stabilization (Sciaena umbra) or are still increasing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 58 publications
4
66
0
Order By: Relevance
“…Most of the partially protected zones considered in this study surround fully protected areas (Appendix A) and may attract fishermen. Full protection enhance fish abundance and size (Guidetti et al, 2014;Sala et al, 2012), often resulting in the spillover of larvae and adults to adjacent unprotected areas (Di Franco et al, 2015;Di Lorenzo et al, 2016;Garcia-Rubies et al, 2013;Goñi et al, 2010;Stobart et al, 2009), hence concentrating fishing effort (Kellner et al, 2007;Stelzenmüller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the partially protected zones considered in this study surround fully protected areas (Appendix A) and may attract fishermen. Full protection enhance fish abundance and size (Guidetti et al, 2014;Sala et al, 2012), often resulting in the spillover of larvae and adults to adjacent unprotected areas (Di Franco et al, 2015;Di Lorenzo et al, 2016;Garcia-Rubies et al, 2013;Goñi et al, 2010;Stobart et al, 2009), hence concentrating fishing effort (Kellner et al, 2007;Stelzenmüller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, this species does not benefit from any specific protection outside of MPAs. In coastal zones with favourable habitats, the presence of S. umbra is considered as an indication of high environmental quality and fish community richness (Mouillot et al, 2002;Garcia-Rubies et al, 2013). Monitoring its population characteristics in both protected (Harmelin and Marinopoulos, 1993;Francour, 1994;Harmelin, 2013) and unprotected areas exposed to all types of fishing reveals trends over time and attests to the fact that the brown meagre can be a useful bioindicator of professional and recreational fishing pressures (Harmelin and Ruitton, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More than a several examples confirmed that it takes five years or more to achieve significant effects of protection, namely in no-take zones, on coastal resources (Guidetti et al 2010, Aburto-Oropeza et al 2011. García-Rubies et al (2013) confirm that fish populations may require decadal time scales to recover from exploitation, both in terms of total abundance and total biomass and that rates of recovery differ between species. However, even with total exclusion of fishing effort, depleted stocks sometimes show little or no recovery over a long time period.…”
Section: Discussionmentioning
confidence: 84%